ANALISIS DESTINATION IMAGE TERHADAP REVISIT INTENTION MELALUI SATISFACTION DAN PLACE ATTACHMENT: LITERATURE REVIEW - Satriawan, Aditya; Abdillah, Yusri; Pangestuti, Edriana (FIA UB, 2022)
ABSTRACT This literature review aims to examine the antecedent factor of one form of tourist loyalty, namely the revisit intention. This study was carried out by searching and filtering articles from reputable journals that match the problem, then presenting relevant theories to the research topic. Based on the results of this literature review, the authors found that destination image, satisfaction, and place attachment were antecedents of revisit intention. The image of a destination received by tourists after making a visit will affect the satisfaction and attachment that occurs between the tourists themselves and the destination visited, which leads to the intention to revisit. This literature review concludes several implications, especially for tourism service providers for their tourist destinations, thus forming a positive image for tourists and leading to the intention to revisit.